Raman spectra of minerals containing interconnected As(Sb)O3 pyramids: trippkeite and schafarzikite - Kharbish,S. (Journal of Geosciences, 2012)
Oriented single-crystals of trippkeite (CuAs2O4) and an isostructural mineral schafarzikite (FeSb2O4) were investigated by polarized Raman spectroscopy. The internal vibrations, i.e. the stretching and bending modes, of trippkeite occur between 250 and 850 cm-1, and those of schafarzikite between 200 and 750 cm-1. The higher mass and the longer bond distances of the SbO3 groups readily explain the lower wavenumbers of the latter. Comparing the spectra of minerals containing XO3 pyramids with those of the minerals from the present study, approximate similarities in the spectral features are evident. A clear distinction between Raman spectra of separated and interconnected (As,Sb)O3 groups is not observed.
Keywords: oriented single-crystals; pyramidal (AsSb)O3 groups; Raman spectroscopy; schafarzikite; trippkeite